Loading

To solve the equation, we need to try to make the second equation all in x first.From the first equation 2x-y=1,we could rewrite it into y=2x-1,Then we put y=2x-1 into the quadratic equation 10x^{2}-y^{2}-x+1=0 to replace y .Then we get 10x^{2}-(2x-1)^{2}-x+1=0Next we expand the equation above, we open the bracket first, then we get10x^{2}-(4x^{2}-4x+1)-x+1=010x^{2}-4x^{2}+4x-1-x+1=0Then we put the same item together, we get6x^{2}+3x=0Then from this equation, we can get the value of X.To solve this one variable quadratic equation, we can find the largest factor 3x3x(2x+1)=0if this equation equals 0,then 3x=0 or 2x+1=0then we can get x=0 or x=-1/2As we know before, y=2x-1to get the value of y, we just need to substitute the value of x.if x=0, then y=-1if x=-1/2, then y=-2